Spruce, pine and fir needles as sustainable ingredients for whole wheat bread fortification: Enhancing nutritional and functional properties - Fidelis, Marina; Tienaho, Jenni; Meneguzzo, Francesco; Pihlava, Juha-Matti; Rudolfsson, Magnus; Järvenpää, Eila; Imao, Haruhiko; Hellström, Jarkko; Liimatainen, Jaana; Kilpeläinen, Petri; Yang, Baoru; Jyske, Tuula (Elsevier, 2024)
This study investigated green needles and fine twigs (NT) from spruce, pine, and fir, widely available forest by-products, as potential functional ingredients and natural preservatives for whole wheat bread fortification. The effects of replacing water with NT extracts at 0, 35, and 70% levels were assessed on bread's secondary metabolite profiling, bioactivity, nutrition, and quality. The NT-bread demonstrated good stability of compounds analyzed by HPLC-DAD after 24 and 72 h, with a notable increase in the content of several polyphenols after 72 h of storage. This increase was correlated closely with an over 80% enhancement in antioxidant activity during storage, suggesting extended shelf-life. A total of 115 compounds were identified by UHPLC-QTOF-MS/MS, including flavonoids, phenolic acids, alkaloids, stilbenes, lignans, resin acids, and gibberellins. Among the substitution levels, 35% , particularly pine NT-fortified bread, was sufficient to enhance functionality while preserving bread quality and sensory acceptability, making it a strong candidate for further development as a bioactive product. Overall, the findings demonstrate the valorization potential of underutilized NT as natural antioxidants and will help provide the industry with phytochemical compositional information. This study highlights the broader applicability of these side streams by employing a green extraction technique (hydrodynamic cavitation) that yields valuable compounds, promotes sustainability, and supports the circular economy through a cost-effective and efficient process.
Keywords: conifer needles; forest side streams; bioactive compounds; functional bread; bread quality